The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1349-7006.2005.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Cepharanthine potently enhances the sensitivity of anticancer agents in K562 cells

Abstract: A major impediment to cancer treatment is the development of resistance by the tumor. P-glycoprotein (P-gp) and multidrug resistance protein 1 (MRP1) are involved in multidrug resistance. In addition to the extrusion of chemotherapeutic agents through these transporters, it has been reported that there are differences in the intracellular distribution of chemotherapeutic agents between drug resistant cells and sensitive cells. Cepharanthine is a plant alkaloid that effectively reverses resistance to anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,705 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…3I) suggests that, as an amphiphilic cation, it may directly enter the lysosomes and modulate pH, an effect similar to that seen with lysosomotropic agents [41]. This possibility has been proposed previously [42]. The dysfunction of lysosomal acidification and an increase in the organelle size is not likely due to the inhibition of NPC1 as another NPC1 inhibitor itraconazole did not change lysosomal size or pH in endothelial cells (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…3I) suggests that, as an amphiphilic cation, it may directly enter the lysosomes and modulate pH, an effect similar to that seen with lysosomotropic agents [41]. This possibility has been proposed previously [42]. The dysfunction of lysosomal acidification and an increase in the organelle size is not likely due to the inhibition of NPC1 as another NPC1 inhibitor itraconazole did not change lysosomal size or pH in endothelial cells (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 63%
“…It has been proposed that CEP is a membrane interacting and stabilizing agent, and this effect may modulate the function of membrane proteins such as V-type ATPase on the lysosomes [55]. In support of this notion, CEP inhibited lysosome acidification in cancer cells and potentiated the effects of weak-base chemotherapy drugs by preventing sequestration of the drugs in the lysosomes [42]. In addition to its anticancer potentiating activity, CEP also showed several beneficial effects on cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…Cepharanthine is known as a membrane-interacting agent with membranestabilizing activity, and is widely used in Japan for the treatment of snake venom-induced hemolysis, nasal allergy, leukopenia induced by anticancer drugs and radiation therapy (6). We previously reported that cotreatment of cepharanthine with doxorubicin and vincristine resulted in the enhancement of cytotoxicity the anti-cancer drugs and the apoptosis induced in K562 cells (15). Cepharanthine also reversed paclitaxel resistance in MRP7-transfected cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…Cepharanthine 89 showed that cepharanthine is an effective agent for the reversal of resistance in human chronic myelogenous leukemia cell line (K562). It has also enhanced the sensitivity to doxorubicin and VCR, and enhanced apoptosis induced by doxorubicin and VCR in K562 cells.…”
mentioning
confidence: 99%